Modelling hydrogen production by the rich combustion of heavy fuel oil. (26th October 2016) - Gómez, J.; Mmbaga, J.P.; Hayes, R.E.; Toledo, M.; Gracia, F.
Abstract: This paper reports on a modelling study of the rich combustion of heavy fuel oil in a reactor packed with an inert porous medium. Decalin is used as a model compound to represent the heavy fuel oil. A computational model is developed for the reactor, based on a two space dimensional transient heterogeneous description, and a kinetic global model for partial oxidation reforming of decalin is proposed. Also, equilibrium calculations were performed for the experimental conditions of the study. The experimental and simulation results show that heavy fuel oil is a potential fuel to produce hydrogen. It is concluded that notable characteristics of the process can be observed by simulation: the presence of an axial maximum in the production of H2, and positive effects of the equivalence ratio and filtration velocity increase and heat losses reduction on the fuel conversion to H2 . Graphical abstract: Highlights: Rich combustion of heavy fuel oil to produce hydrogen using experiment and model. Filtration combustion in an inert packed bed is used. Decalin is used as a model compound to simulate the process. A global kinetic model is proposed for the rich combustion of decalin.